2003
DOI: 10.1152/jn.01043.2002
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Correlates of Intrinsic Electrical Excitability in Neurons of the Deep Cerebellar Nuclei

Abstract: phological correlates of intrinsic electrical excitability in neurons of the deep cerebellar nuclei. J Neurophysiol 89: 1738 -1747, 2003; 10.1152/jn.01043.2002. To what degree does neuronal morphology determine or correlate with intrinsic electrical properties within a particular class of neuron? This question has been examined using microelectrode recordings and subsequent neurobiotin filling and reconstruction of neurons in the deep cerebellar nuclei (DCN) of brain slices from young rats (P13-16). The neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 36 publications
5
64
0
Order By: Relevance
“…These studies triggered a host of experimental studies that are consistent with the idea that nervous systems must balance the mechanisms that allow them to be plastic with others that maintain their stability (5,40,41,43). Subsequently, both theoretical and experimental studies showed that there are multiple solutions consistent with very similar activity patterns (31,37,(44)(45)(46)(47). It is important to recognize that homeostatic tuning rules, such as those studied here, do not invariably produce the same set of channel densities, but instead result in a target activity that is consistent with a range of solutions.…”
Section: Discussionmentioning
confidence: 79%
“…These studies triggered a host of experimental studies that are consistent with the idea that nervous systems must balance the mechanisms that allow them to be plastic with others that maintain their stability (5,40,41,43). Subsequently, both theoretical and experimental studies showed that there are multiple solutions consistent with very similar activity patterns (31,37,(44)(45)(46)(47). It is important to recognize that homeostatic tuning rules, such as those studied here, do not invariably produce the same set of channel densities, but instead result in a target activity that is consistent with a range of solutions.…”
Section: Discussionmentioning
confidence: 79%
“…Large glutamatergic neurons project to the premotor nuclei, medium-to-large GABAergic neurons project to the inferior olive, and small GABAergic and/or glycinergic interneurons project their axons locally, although some have claimed that the local projections are collaterals of GABAergic axons that innervate the olive (Batini et al, 1992;De Zeeuw and Berrebi, 1995). In the present study, we performed whole-cell patch recordings from neurons with somatic diameter larger than 20 m. Hence, the majority of neurons in the present study are presumably glutamatergic projection neurons (Batini et al, 1992;De Zeeuw and Berrebi, 1995;Aizenman et al, 2003). In addition to the glutamatergic projection neurons, it will also be interesting to investigate whether the mossy fiber synapses onto inhibitory neurons in the DCN can also express LTD or LTP.…”
Section: Discussionmentioning
confidence: 81%
“…The position of the interpositus nuclei was identified in the slices using a 5ϫ objective mounted on an upright microscope (Axioskop 2 FS; Zeiss, Oberkochen, Germany), and DCN neuron somata were then visualized through a 40ϫ water immersion objective using infrared differential interference contrast optics. In the present study, recordings were made from large neurons with somatic diameter larger than 20 m, most of which are thought to correspond to the glutamatergic projection neurons of the cerebellar nuclei (Batini et al, 1992;De Zeeuw and Berrebi, 1995;Aizenman et al, 2003). It is possible, however, that a small number of our recordings were from the largest of the DCN GABAergic inhibitory projection neurons.…”
Section: Methodsmentioning
confidence: 93%
“…3A-C). Glutamatergic projection neurons were evidenced by their large size (Chan-Palay, 1977;Kumoi et al, 1988;Batini et al, 1992;Aizenman et al, 2003). In contrast to other brain areas in the DCN, it is the large neurons that are relatively fast spiking (Uusisaari et al, 2007).…”
Section: Altered Properties Of Kcnc Allele-deficient Dcn Neuronsmentioning
confidence: 99%